2022
DOI: 10.21608/ejhc.2022.266524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate Knowledge & Practice of Nurses Regarding Care of Women with Cesarean Section

Abstract: Background: Nurses had play a multidisplinary role as a direct care provider who must provide competent nursing care based upon evidence base research finding for women undergoing cesarean section. Aim: evaluate knowledge & practice of nurses regarding care of women with cesarean section Study Design: descriptive design. Setting: the study was conducted at 6 inpatient units' at maternity hospital Ain shams University. Sampling: purposive sample included 38 nurses. Tools of data collection: were structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Regarding nurses' performance in caesarean section care, there was highly statistically significant difference between pre and post intervention for nurses regarding practical skills of caesarean section care. This result comes in agreement with Sayed et al, (2022) who revealed that nearly two thirds of the studied sample had incorrect practical skills within Two hours post caesarean section and more than half of the studied sample had incorrect practical skills about nursing care for caesarean section. Also, these results agree with El-Khawaga et al, (2019) who revealed that there was highly significant between total practices of studied nurses and their knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding nurses' performance in caesarean section care, there was highly statistically significant difference between pre and post intervention for nurses regarding practical skills of caesarean section care. This result comes in agreement with Sayed et al, (2022) who revealed that nearly two thirds of the studied sample had incorrect practical skills within Two hours post caesarean section and more than half of the studied sample had incorrect practical skills about nursing care for caesarean section. Also, these results agree with El-Khawaga et al, (2019) who revealed that there was highly significant between total practices of studied nurses and their knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…This result comes in agreement with Fatthy & Tolba, (2021) who showed that slightly less than three quarters of studied sample had inadequate knowledge regarding CS and its management before implementing nursing management intervention but after implementing nursing management their knowledge improved. Also Sayed et al, (2022) added that more than half of the studied sample had incorrect knowledge regarding to complications & reasons for CS respectively and more than three quarters of studied sample had incorrect knowledge about nursing care for caesarian section. These findings were supported by Hussien et al, (2021) who carried out a quasi-experimental (pre post-test) to assess the "Impact of enhanced recovery pathway application outcomes on nurses and women undergoing cesarean section" in a rural area in Egypt and found that nurses' knowledge of all aspects of the CS had improved which enhanced women recovery.…”
Section: Discussionmentioning
confidence: 99%